ANALISIS PENDAPATAN PETANI PADA BERBAGAI TIPE USAHATANI KARET DI DAS BATANG PELEPAT KABUPATEN BUNGO, JAMBI - Sunarti Sunarti (University of Jember, 2009)
Land in Batang Pelepat watershed were generally cultivated for rubber farming. The objectives of this research are to identify characteristics of rubber farming systems types and analysis their effect on farmer’s income. This research was carried out by survey method and data were analyzed using descriptive analysis. The results of the research showed that rubber farming systems in Batang Pelepat watershed were not able to fulfill indicators of feasible income. Keyword: Rubber, Farming, Income, Watershed